The burning of Rosemont Abbey [large type] - Stephens, Naomi (Center Point Large Print, 2024)
"1956: In a quiet English village, the smoldering ruins of Rosemont Abbey have set the residents' tongues wagging, and everyone is quick to accuse troublemaker Paul Everly of the crime of arson. Paul has vanished without a trace, leaving only his plucky twin sister, Louisa, certain of his innocence. Fueling her conviction is an inexplicable connection -- she felt her twin's death an hour before the abbey went up in flames. Armed with nothing but her wit and her keen sense of intuition, Louisa embarks on her own investigation, challenging the dubious townspeople and the disdain of her aunt and uncle. Even Inspector Malcolm Sinclair, once Paul's closest friend, warns Louisa to abandon her pursuit. But Louisa is determined to solve a murder no one else believes was committed, even if it means unraveling secrets that could shake Wilbeth Green to its core."--